Altered Frequencies and Functions of Innate Lymphoid Cells in Melanoma Patients Are Modulated by Immune Checkpoints Inhibitors - Cristiani, Costanza Maria; Capone, Mariaelena; Garofalo, Cinzia; Madonna, Gabriele; Mallardo, Domenico; Tuffanelli, Marilena; Vanella, Vito; Greco, Marta; Foti, Daniela Patrizia; Viglietto, Giuseppe; Ascierto, Paolo Antonio; Spits, Hergen; et al. (Frontiers in Immunology, 2022)
Monoclonal antibodies targeting immune checkpoints improved clinical outcome of patients with malignant melanoma. However, the mechanisms are not fully elucidated. Since immune check-point receptors are also expressed by helper innate lymphoid cells (ILCs), we investigated the capability of immune checkpoints inhibitors to modulate ILCs in metastatic melanoma patients as well as melanoma cells effects on ILCs functions. Here, we demonstrated that, compared to healthy donors, patients showed a higher frequency of total peripheral ILCs, lower percentages of CD117+ ILC2s and CD117+ ILCs as well as higher frequencies of CD117- ILCs. Functionally, melanoma patients also displayed an impaired TNFα secretion by CD117- ILCs and CD117+ ILCs. Nivolumab therapy reduced the frequency of total peripheral ILCs but increased the percentage of CD117- ILC2s and enhanced the capability of ILC2s and CD117+ ILCs to secrete IL-13 and TNFα, respectively. Before Nivolumab therapy, high CCL2 serum levels were associated with longer Overall Survival and Progression Free Survival. After two months of treatment, CD117- ILC2s frequency as well as serum concentrations of IL-6, CXCL8 and VEGF negatively correlated with both the parameters. Moreover, melanoma cells boosted TNFα production in all ILC subsets and increased the number of IL-13 producing ILC2s in vitro. Our work shows for the first time that PD-1 blockade is able to affect ILCs proportions and functions in melanoma patients and that a specific subpopulation is associated with the therapy response.